Natural and economic selection: Lessons from the evo-devo and multilevel selection debate - Georg Schwesinger (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
This paper sheds new light on the concept of selection in evolutionary economics. The interpretation of natural evolution has experienced significant changes in the last decades, while these developments have been often ignored by economists. This is especially true for the concept of selection, a key concept in many evolutionary approaches. In economics as well as in biology, selection is seen as a central mechanism, which mediates for example the spread of information and innovation, the coordination of groups of agents and the optimization of their behavior. In this article we are aiming to explore the actual significance of selection as a major explanatory principle in economics. Starting with an analysis of a modern and modified understanding of the selection mechanism in nature we will draw some conclusions for its use in economics.
Keywords: B15; B40; B52; D03; 330; Selection; Bioeconomics; Evo-Devo; Cultural Evolution; Multilevel Selection